Genetic Diversity of Various Goat Breeds in East Java Based on DNA Microsatellite Markers - T. E. Susilorini; D. Wulandari; A. Furqon; W. A. Septian; F. Saputra; S. Suyadi (Tropical Animal Science Journal, 2022)
Information on genetic diversity using microsatellite markers was essential to formulate effective conservation and breeding strategies. This study aims to identify the genetic diversity and relationships between Kacang, Senduro, Peranakan Ettawa (PE), Boer, and Saanen goats in the East Java region, Indonesia, using 12 microsatellite markers. A total of 86 goat blood DNA samples, which consisted of Kacang (n=41), Senduro (n=23), Boer (n=13), PE (n=5), and Saanen (n=4), were used in this study. The DNA was extracted based on Genomic DNA Mini Kits protocols for analysis fragment in microsatellite DNA region using specific primer recommended by the ISAG/FAO. A total of 96 alleles were identified in this study. The observed heterozygosity ranged from 0.470±0.135 (Kacang) to 0.592±0.211 (PE) and the expected heterozygosity ranged from 0.589±0.251 (Saanen) to 0.762±0.084 (PE). F statistical analysis include inter-population inbreeding rate (Fis) 0.2583 (25.83%), inbreeding rate in population (Fit) 0.3238 (32.38%), and genetic differentiation (Fst) 0.0882 (8.82%). The 11 microsatellite markers were highly informative (PIC>0.5), except the INRA063 locus markers were quite informative (PIC 0.25-0.5). The research showed that Kacang, Senduro, and PE goats had a close genetic distance and formed a cluster. Kacang and Saanen goats showed a long genetic distance at 26.9%. In conclusion, the genetic relationship among goat breeds in East Java was divided into three clusters where Boer and Saanen goats formed their cluster.